Association between social integration and medical returns among the migrant elderly following children to Jinan City China - Jinfeng Zhao; Fanlei Kong; Shixue Li (BMC, 2021)
Abstract Background Studies had shown that social integration was related to the utilization of medical services. Few studies investigated the relationship between social integration and medical returns among the elderly. None research had ever clarified the effect of social integration on medical returns among the migrant elderly following children (MEFC) to new cities. This study aimed to explore the association between social integration and medical returns among the MEFC in Jinan, China. Method This cross-sectional study included 627 MEFC in Jinan China. Social integration was evaluated by economic integration, acculturation, and identification. Medical return was assessed by asking the subjects whether go back to hometown to use the medical services when ill. Chi-squared test and multivariable logistic regression were applied to analyze the association between social integration and medical returns of the MEFC. Results and discussion It was found that 20.3% of the MEFC had a medical return. As for social integration, those who had not joined local medical insurance (OR = 3.561, 95% CI 1.577-8.039, p = 0.002) and were unwilling to stay for a long time (OR = 2.600, 95% CI 1.620-4.174, p = 0.001) were more likely to have a medical return. Furthermore, our findings showed that the MEFC who were accompanied by one or more (OR = 1.568, 95% CI 1.027-2.392, p = 0.037) were more likely to have a medical return than those who migrated alone. Conclusion Negative relationship between social integration and medical returns was found among the MEFC, which means the better social integration of the MEFC would generally have fewer medical return, as well as the better refunding connections of the medical insurance between the current residence and hometown.